Diet composition of sergestid shrimp Acetes serrulatus from the coastal waters of Kukup, Johor, Malaysia. - Oh, S. Y; Arshad, Aziz; Bujang, Japar Sidik; Abd Aziz, Nor Azwady; Nurul Amin, Sanker Mohammad (Academic Journals, 2011)
Shrimps of the genus Acetes Milne-Edwards, 1980 are ecologically and commercially important. The diet composition of A. serrulatus were examined based on 370 specimens collected in the coastal waters of Johor, Peninsular Malaysia from April 2008 to April 2009. The food items in the gut of A. serrulatus were comprised of phytoplankton, zooplankton, plant matter, appendages of decapods, debris and unidentified fragments. Majority of the stomach sacs examined (88.72%) were filled up with food while only 11.28% were found empty. Based on the Simple Resultant Index (% Rs), appendages of decapod (31.87%) was found to be the primary food items, followed by plant matter (16.48%) and zooplankton (14.18%). Thus, it could be concluded that A. serrulatus is omnivorous and feed on phytoplankton, zooplankton and microcrustacean.